Effect of Bovatec and Ralgro implants on finishing steer performance - Lyle W. Lomas (Kansas Agricultural Experiment Station Research Reports, 1982)
Cattle fed Bovatec consumed 17.4% less feed and were 17.7% more efficient than controls, with no effect on gain. Ralgro implants improved gain 12% and feed efficiency 6.9%, with no effect on feed intake. Bovatec and Ralgro combined had an additive effect on feed efficiency.
Keywords: Cattlemen' s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Implants; Bovatec; Ralgro; Steer performance